Strategi Implementasi Kurikulum Merdeka Belajar di SMA Negeri 10 Palembang - Dewi Moulina; Bukman Lian; Muhammad Juliansyah Putra (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to describe and analyze the strategy for implementing Merdeka Belajar's curriculum, the learning process, and the obstacles that arise. This study uses a descriptive qualitative research method. Informants taken in this study were ten people who were directly related to this research. Data collection techniques used observation, interviews, and documentation. Data analysis used data reduction, data display, and conclusions. The results showed that the strategy for implementing of kurikulum merdeka belajar which was carried out in stages at SMA Negeri 10 Palembang went very well; Likewise, the intracurricular, co-curricular and project learning processes in the independent learning curriculum are going well; Problems that arise in the implementation of the independent learning curriculum are the lack of teacher competence, lack of basic literacy competencies in studentssesuai, book references and internet access have been overcome by means of teacher training, completing book references and internet access which has been running very well. Conclusion, The strategy for implementing the independent learning curriculum at SMA N 10 Palembang has been implemented with careful planning and carried out in stages from the adoption route of implementing the independent learning curriculum, webinar series, help service center (Helpdesk), independent teaching platform, learning community and resource persons sharing practices Good. Keywords: strategy of implementation, kurikulum merdeka belajar, quality of learning